Marketing Strategy in Building Brand Image of New Coffee Shop: Qualitative Study on KLCR Coffee North Jakarta - Alya Nurrima Syifa (Golden Ratio of Data in Summary, 2026)
The increasingly fierce competition in the coffee shop industry demands that businesses, including new coffee shops, implement appropriate marketing strategies to build brand image from the early stages of operation. This study aims to analyze the marketing strategy implemented by KLCR Coffee, a new coffee shop in North Jakarta, and its role in building brand image in the minds of consumers. This study used a qualitative approach with a case study method. Data were collected through in-depth interviews with management and consumers, direct observation, and documentation. Research informants were selected using a purposive sampling technique. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing, supported by source and technique triangulation to ensure data validity. The results show that KLCR Coffee's marketing strategy, which includes product, price, place, and promotion, is still simple and not optimal. However, this strategy plays a role in shaping the initial brand image, especially through product quality and location proximity to the local community. KLCR Coffee's brand image is reflected in the level of brand recognition that is still limited, the brand association as a simple coffee shop, and the perception of quality that is considered appropriate to the price. This research provides practical implications for new coffee shops in formulating consistent marketing strategies as well as academic contributions to marketing studies in small-scale businesses.